Menegosiasikan Idealisme dan Keberlanjutan dalam Kewirausahaan Sosial: Perspektif Sosiologi Ekonomi dan Kewirausahaan - Mildayanti Mildayanti; Damas Gianlugi Alrizqi; Rahmat Hidayat (PENSOS : Jurnal Penelitian dan Pengabdian Pendidikan Sosiologi, 2026)
Social entrepreneurship cannot be fully understood through a management and business-strategy lens alone; it also requires a sociological lens to capture the dimensions of social embeddedness, capital, and legitimacy surrounding social entrepreneurial practice. This conceptual article examines how the tension between social idealism and business sustainability is negotiated by social entrepreneurs by combining perspectives from economic sociology particularly social embeddedness and Bourdieu's capital-habitus-field triad with entrepreneurship theory on hybrid organizing and mission drift. Through a narrative literature review of publications from the last five years, this article shows that social entrepreneurs' idealism can be understood as a form of social embeddedness within networks and institutional structures, while business sustainability requires the accumulation of sufficient economic, social, and symbolic capital within the entrepreneurial field. Mission drift, in this framework, is reinterpreted as a process of disembeddedness, whereby the organization becomes detached from its social ties and community values due to the dominance of market logic. The article further connects these findings to the context of MSME-based social entrepreneurship in Indonesia, which is sustained by local social capital such as mutual cooperation (gotong royong) and community networks, and outlines implications for developing sociologically informed social entrepreneurship education in higher education.